Annual Plan 1991-92 - Planning Commission (Planning Commission, 1991)
In the last few years, the Indian Economy has witnessed reasonably good growth. During the Seventh Plan period, GDP grew at an average rate of 5.6 percent per year (table 1.1). During 1990-91, inspite of the Gulf Crisis, the economy is estimated to have grown at about 5.0% with GDP from agriculture and industry growing at 1.1 per cent and 7.6 per cent respectively. Growth is GDP during the eighties in general and during the last few years in particular has been significantly higher than the trend rate of growth of about 4% achieved during the previous three decades. The growth performance during the last few years, thus, has been commendable.
Government of India Planning Commission
Government of India Planning Commission